The Acceleration Principle Reconsidered - Eckaus, R. S. (Quarterly Journal of Economics, 1953)
I. Introduction, 209. — II. Theoretical development of the acceleration principle, 211. — III. Critical appraisal of the acceleration principle, 216. — IV. Other forms of the acceleration principle, 221.